Automatic generation and discretization of fully periodic representative volume elements of plain woven composites. (December 2018) - Jendrysik, Nadine; Schneider, Konrad; Bargmann, Swantje
This paper introduces an efficient and simple method to automatically generate and mesh geometrically parametrized representative volume elements for plain woven fiber-reinforced composites. The presented approach is capable of generating representative volume elements with 10%–55% fiber volume fraction. The practical feasibility of the model is demonstrated on numerical examples for isotropic and anisotropic tow materials which are compared to analytical solutions.